Analysis of Land Use Suitability Towards Detailed Spatial Plan (Case Study: Kuta Selatan District, Badung Regency, Bali) - M. Abdul Basyid; Didiek Setiadi Ulumuddin (Jurnal Serambi Engineering, 2023)
South Kuta District is located in the south of Badung Regency, precisely at 8º46'58.7" latitude and 115º05'00"-115º10'41.3" east longitude, at an altitude of 0-200 meters above sea level. South Kuta District administratively consists of Pecatu Village, Ungasan Village, Kutuh Village, Benoa Village, Jimbaran Village, and Tanjung Benoa Village, the existing Village is further divided into 62 banjars or neighborhoods. The development of the South Kuta District must be balanced with the supervision of space utilization so that space utilization remains balanced. Hence, it is necessary to monitor the Geographic Information System (GIS) related to land use against the current RDTR plan. The methodology in this study includes SHP data collection, map overlays, map layouts to make spatial pattern maps, land use maps, and land suitability maps. This research was conducted in South Kuta District, Badung Regency, Bali. In this study, the land use map uses the results of overlaying SHP data from the administration of the South Kuta District, the South Kuta District Administration, and the RDTR of the South Kuta District in 2018. From this research, the largest zone in South Kuta is the tourism zone with an area of 3123,429494 Ha and the largest land use is in Kuta. South is mixed use with an area of 1100.442 Ha with suitable land ie 9817.426 Ha and unsuitable land, namely 325,186 Ha.